1976
DOI: 10.1128/jb.127.3.1529-1537.1976
|View full text |Cite
|
Sign up to set email alerts
|

Simple agarose gel electrophoretic method for the identification and characterization of plasmid deoxyribonucleic acid

Abstract: Argarose gel electrophoresis may be employed effectively for the detection and preliminary characterization of plasmid deoxyribonucleic acid (DNA) present in clinical isolates and laboratory strains of gram-negative microorganisms. The method is sensitive and does not require radioisotopes or ultracentrifugation. The estimation of plasmid mass from the extent of DNA migration in gels compares favorably with results obtained by electron microscopy of plasmid DNA purified by equilibrium density centrifugation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
314
0
1

Year Published

1977
1977
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,063 publications
(322 citation statements)
references
References 14 publications
7
314
0
1
Order By: Relevance
“…Plasmid DNA samples were electrophoresed through 0·7% agarose in TBE buffer (Meyers et al 1976). The gels were stained with ethidium bromide solution, discoloured in water, and photographed.…”
Section: Plasmid Analysismentioning
confidence: 99%
“…Plasmid DNA samples were electrophoresed through 0·7% agarose in TBE buffer (Meyers et al 1976). The gels were stained with ethidium bromide solution, discoloured in water, and photographed.…”
Section: Plasmid Analysismentioning
confidence: 99%
“…Arguably the best understood mobile genetic elements are plasmids, which have been widely studied in S. aureus and MRSA since the 1970s [7][8][9][10]. Currently, it is suggested that more than 90% of MRSA strains carry plasmids while numerous studies have supported the important role plasmids play in staphylococcal multidrug-resistance [7,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…1). In contrast to the results of previous were identified by their sub-division into two workers (Meyers et al 1976 Molecular weights were calculated using the plasmids RIGQ-I, RPI, R388, pSC134, pHV14 and pBR322 as molecular weight standards. oc DNA bands were identified by a modification of the method of Hintermann et al (1981).…”
Section: Form (Ccc) and Open Circular (Oc) Form Thusmentioning
confidence: 99%